2022
DOI: 10.1007/s41347-022-00263-5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Components of Therapeutic Alliance and Well-Being from Use of a Global Digital Mental Health Benefit During the COVID-19 Pandemic: Longitudinal Observational Study

Abstract: Digital mental health services leverage technology to increase access to care, yet less is known about the quality of therapeutic relationships in a virtual setting. This study examined components of therapeutic alliance (a mechanism underlying successful treatment) and its association with beneficial treatment outcomes in a real-world, virtual setting. The objective is to examine (1) participant ratings of components of therapeutic alliance with providers in a virtual setting, (2) changes in subjective well-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…[17][18][19] Furthermore, the resultant increase in physical stress may lead to anxiety, depression, and sleep disorders. [20][21][22] In the Fangcang shelter hospital, there is continuous bright light intensity even at night. Most patients with SARS-CoV-2 infection already exhibit respiratory symptoms such as cough and fever, and gastrointestinal symptoms such as nausea, anorexia, and diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Furthermore, the resultant increase in physical stress may lead to anxiety, depression, and sleep disorders. [20][21][22] In the Fangcang shelter hospital, there is continuous bright light intensity even at night. Most patients with SARS-CoV-2 infection already exhibit respiratory symptoms such as cough and fever, and gastrointestinal symptoms such as nausea, anorexia, and diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic alliance, a positive relationship between patient and therapist, is a reliable predictor of better mental health treatment outcomes 3 , 4 , and even affects the efficacy of psychological treatments delivered in digital forms 5 – 7 . Similarly, patient belief in the credibility of a therapy offered, and expectations of successful outcomes, predict better treatment outcomes 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Emerging research on the impact of COVID‐19 on the therapeutic alliance has suggested what was vital to successfully navigating therapy during the pandemic (Cioffi et al ., 2020; Fernández‐Álvarez & Fernández‐Álvarez, 2021; Geller, 2021; Grignoli, Arnaboldi & Antonini, 2021; Zubala & Hackett, 2020; van Lotringen et al ., 2021). Several studies found that therapeutic alliance was not significantly altered by online therapy delivery (Earle & Freddolino, 2022; Eichenberg et al ., 2022; Lange et al ., 2022; Leuchtenberg, Gromer & Käthner, 2023; Sagui‐Henson et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%